Pengaruh Fasilitas Belajar dan Lingkungan Keluarga Terhadap Motivasi Belajar IPS Kelas IV Sekolah Dasar - Laoli, Natal Elviana; Zendrato, Putri Sejahtera; Waruwu, Welman Kristian; Zendrato, Fani Obertin; Hia, Sofiani; Waruwu, Datatuwu Pratama; Zebua, Rohani Handayani; Gulo, Syanti Maria; Harefa, Edward (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to analyze the influence of learning facilities and family environment on the social science (IPS) learning outcomes of class IV students. This research was conducted using quantitative research methods, where data was collected through questionnaires distributed to 78 students at SDN 071015 Alo'oa. The data that has been obtained is then analyzed using validity tests, classical assumption tests, hypothesis tests and multiple linear regression techniques to determine relationships and contribution of each independent variable to the dependent variable. The research results show that learning facilities have a significant and positive influence on students' social studies learning outcomes. Apart from that, the family environment was also found to have a significant influence on social studies learning outcomes. Family support, whether in the form of motivation, academic guidance, or providing learning resources, has been proven to improve student learning achievement